1994
DOI: 10.1021/jm00039a004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amine Substituents on 5-HT2A versus 5-HT2C Binding of Phenylalkyl- and Indolylalkylamines

Abstract: The effect of 15 different amine substituents on 5-HT2A and 5-HT2C serotonin receptor binding was investigated for two series of compounds (i.e., phenylalkylamine and indolylalkylamine derivatives). In general, amine substitution decreases receptor affinity; however, N-(4-bromobenzyl) substitution results in compounds that bind at 5-HT2A receptors with high affinity (Ki < 1 nM) and with > 100-fold selectivity. Although parallel structural modification in the two series result in parallel shifts in 5-HT2C bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 7 publications
3
75
0
Order By: Relevance
“…We recognized, therefore, that the aromatic ring of the N- benzyl moiety was enhancing activity through some specific biophysical property, which we believe to be a -interaction with an aromatic residue in the receptor. These data are consistent with a previous study evaluating amine substitution on phenylalkylamines and indolealkylamines (Glennon et al, 1994). In that study, however, N-arylmethyl analogs of the phenethylamine 2C-B showed only ϳ2-to 3-fold increased affinity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We recognized, therefore, that the aromatic ring of the N- benzyl moiety was enhancing activity through some specific biophysical property, which we believe to be a -interaction with an aromatic residue in the receptor. These data are consistent with a previous study evaluating amine substitution on phenylalkylamines and indolealkylamines (Glennon et al, 1994). In that study, however, N-arylmethyl analogs of the phenethylamine 2C-B showed only ϳ2-to 3-fold increased affinity.…”
Section: Discussionsupporting
confidence: 92%
“…Although these novel agonists were characterized in a rat-tail artery model, we decided to examine whether these N-benzyl and related analogs had high affinity and potency in our heterologous cell-based assay systems. Furthermore, because N-alkyl substitution was known to abolish hallucinogenic activity and binding affinity of phenethylamines (Shulgin and Shulgin, 1992;Glennon et al, 1994), we were particularly curious about the contribution of the N-benzyl group, which seemed most likely to be ainteraction of some type with an aromatic residue within the receptor.…”
mentioning
confidence: 99%
“…N-alkylation or N,N-dialkylation proved detrimental to the potency of most phenylalkylamines. [172,174,175] An exception was found in a series of N-benzyl substituted phenylalkylamines; [176] affinity studies comparing 2C-B (11) with its N-benzylated analogues (29-31) revealed an approximate twofold increase in binding affinity for [ 125 I]DOI labeled 5-HT 2A receptors. Moreover compounds 29-31 showed increased subtype selectivity (> 100 fold) for 5-HT 2A over 5-HT 2C receptors, however the question whether 29-31 act as agonists or antagonists has not been addressed.…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%
“…Moreover compounds 29-31 showed increased subtype selectivity (> 100 fold) for 5-HT 2A over 5-HT 2C receptors, however the question whether 29-31 act as agonists or antagonists has not been addressed. [176] Another study showed that a series of related N-benzyl analogues act as potent partial agonists in vascular in vitro models. [177][178][179] The N-(2-methoxybenzyl) analogue 32 (25I-NBOMe) of 2C-I (12) was an extremely potent partial 5-HT 2A agonist (EC 50 = 0.0813 nm; 30 % of 5-HT stimulation) compared with DOI (17, EC 50 = 7.41 nm; 68 % of 5-HT stimulation) in the same model.…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%
“…[3][4][5][6] Though drawing less scrutiny than better known psychedelics like LSD or psilocybin, strictly speaking these are not novel materials. [7,8] In contrast, N-benzyl phenylethanamines progressed from earliest published reports [9][10][11][12][13][14] and subsequent research [15,16] to ready grey-market availability and ultimately prohibition -in the UK [17,18] and the USA [19] -in less than 20 years.…”
Section: Introductionmentioning
confidence: 99%